Electroacupuncture and Moxibustion-Like Stimulation Relieves Inflammatory Muscle Pain by Activating Local Distinct Layer Somatosensory Afferent Fibers - Chen, Lizhen; Wang, Xiaoyu; Zhang, Xiaoning; Wan, Hongye; Su, Yangshuai; He, Wei; Xie, Yikuan; Jing, Xianghong (Frontiers in Neuroscience, 2021)
Recent studies have shown that both superficial and deep acupuncture produced clinically relevant and persistent effect on chronic pain, and several subtypes of somatic primary afferents played critical roles in acupuncture and moxibustion analgesia. However, which kind of primary afferents in the superficial and deep tissue of the acupoint is activated by acupuncture or moxibustion to relieve pain persistently remains unclear. The aim of this study is to investigate the roles of distinct peripheral afferents in different layers of the tissue (muscle or skin) in the acupoint for pain relief. Muscular A-fibers activated by deep electroacupuncture (dEA) with lower intensity (approximately 1 mA) persistently alleviated inflammatory muscle pain. Meanwhile, cutaneous C-nociceptors excited by noxious moxibustion-like stimulation (MS) and topical application of capsaicin (CAP) on local acupoint area produced durable analgesic effect. Additionally, spontaneous activity of C-fibers caused by muscular inflammation was also inhibited by dEA and CAP. Furthermore, decreases in pain behavior induced by dEA disappeared after deep A-fibers were demyelinated by cobra venom, whereas CAP failed to relieve pain following cutaneous denervation. Collectively, these results indicate that dEA and MS ameliorate inflammatory muscle pain through distinct primary afferents in different layers of somatic tissue; the former is achieved by activating muscular A-fibers, while the latter is mediated by activating cutaneous C-fibers.